Prone Position Improve Physiological Parameters of Preterm Infants Weaning from CPAP: A Randomized Control Trial - Ayu Ferissa Simorangkir; Yeni Rustina; Defi Efendi (Faculty of Nursing Universitas Padjadjaran, 2021)
The need for continuous positive airway pressure (CPAP) was vital for preterm infant with respiratory distress, but the impact of long-term use was very harmful. The effort to do weaning must be done and facilitate the infant to adapt wean off CPAP. The effect of positioning on stabilized physiological parameters may help preterm infant to adapt under gradual weaning from CPAP. Aim in this study to determine the effect of prone positioning on physiological parameters in preterm infants under gradual weaning CPAP. From Mei to September 2020 total sample 60 preterm infants on non-invasive ventilation or CPAP were randomized into prone position (intervention group, n = 30) and supine position (control group, n = 30). Oxygen saturation, respiratory and heart rate between groups were compared. In the prone position was significant higher than supine position at 30th minute. The mean oxygen saturation in the prone position (99.87±0.35) was higher than in the supine position (97.63±1.45; p=0.001), the mean respiratory rate in the prone position (42.10±8.59 breaths/min) was lower than in the supine position (53.20±6.24 breaths/min; p=0.001), and the mean heart rate in the prone position (144.63±13.07/beats/min) was lower than in the supine position (153.53±10.02/beats/min; p=0.001), so that the prone position can be applied to increase oxygen saturation and to maintain the stability of respiratory rate in preterm infants during gradual weaning. The failure to wean off CPAP (re-CPAP) in the prone group was less frequent which is 3 respondents (5% versus 10%). However, there is no relation between positioning and re-CPAP (p=0.472).